Analysis of household saving factors in Bosnia and Herzegovina: Application of ARDL methodology - Irma idelija (Economic Review: Journal of Economics and Business, 2020)
Most papers in the field of private saving deal with the analysis of private saving as a whole without special consideration of its individual components. This paper is, therefore, focused on the analysis of one of the components of private saving and its factors, and that is the household saving. The analysis was conducted on household saving in Bosnia and Herzegovina (BiH), which, viewed as the sum of saving and time deposits, recorded a cumulative growth of 97% from the outbreak of the global financial crisis until September 2016. The aim of this research is to determine which factors favored the positive trends of household saving in BiH in the period 2000q1-2016q3. As a methodological tool for achieving the research goal and testing the defined hypothesis, the ARDL methodology was used. By applying the ARDL methodology, the work hypothesis was confirmed. Macroeconomic factors have an impact on household saving in BiH.
Keywords: C32; E21; 330; household saving; household saving factors; ARDL methodology